1928
DOI: 10.1001/archpedi.1928.01920210088010
|View full text |Cite
|
Sign up to set email alerts
|

The Fate and Development of the Immature and of the Premature Child

Abstract: About 55 per cent of immature infants live until the end of the first year; 52 per cent reach the school age, and 51 per cent reach the age of puberty; in other words, the mortality after the school age is not any higher than for mature children. This is not true, unfortunately, of the physical as well as of the mental development of the immature infant.Ylpp\l=o"\, in his calculations, always referred to the conception age, i. e., to the intra-uterine and extra-uterine age of the child. He calculated the intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1930
1930
1959
1959

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…Capper (1928) thought that during the first year a premature child has little resistance to infection of the respiratory tract, whereas after the first year his resistance is not unlike that of a mature child. Mohr and Bartelme (1934) likewise noted the frequent occurrence of respiratory infections, particularly colds, among the prematurely born.…”
Section: (D) Nfections Of the Upper Respiratory Tractmentioning
confidence: 99%
“…Capper (1928) thought that during the first year a premature child has little resistance to infection of the respiratory tract, whereas after the first year his resistance is not unlike that of a mature child. Mohr and Bartelme (1934) likewise noted the frequent occurrence of respiratory infections, particularly colds, among the prematurely born.…”
Section: (D) Nfections Of the Upper Respiratory Tractmentioning
confidence: 99%
“…Hess and others (1934) found that the incidence of conunon contagious diseases of childhood did not differ in premature and full-term children, though there seemed to be a more frequent occurrence of respiratory infections, especially 'frequent colds' and pneumonia, in the premature group. Capper (1928) also found a 77 ARCHIVES OF DISEASE IN CHILDHOOD deraed resistance to infection, especially of the respiratory tact, in prematurely born children, chiefly in the first year of life. Pya examitiom.…”
Section: Studies In Prematuritymentioning
confidence: 94%
“…A number of them exhibited nervous symptoms such as nocturnal enuresis, speech disorders, or night terrors. Capper (17) observed " . .…”
Section: The Hypothesis and The Literaturementioning
confidence: 99%